An investigation on the diagnostics and prognostic capabilities of acoustic emission (AE) on a spur gearbox - Tan, Chee Keong (Cranfield University, 2005)
The aim of this research project is to explore a new technique, Acoustic Emission (AE), on both the diagnostic and prognostic capabilities in monitoring gear teeth degradation (pitting), and compare with the more widely used techniques such as vibration monitoring and Spectrometric Oil Analysis (SOA). Furthermore, by employing the experimental results and past literature, a model in predicting the amount of gear surface pitting wear using AE activity level was proposed. The successful forinulation of this proposed model may be able to predict the remaining life of the gear after pitting has been detected, thereby allowing timely replacement to be carried out without the risk of catastrophic failure. A series of experimental tests which include seeded defect simulations, study on the effect of operating parameters over AE (under isothermal conditions), AE source determination tests and accelerated gear fatigue tests have been performed to investigate the diagnostics and prognostics capabilities of AE via a back-to-back gearbox set up. The experimental results achieved have highlighted some significant findings: (a) The variation in rotating speeds, change the AE levels in a much significant amount as compared to the same variation in applied load. (b) The prime source of AE was postulated to be asperity contact under rolling and sliding of the meshing gear teeth surfaces. (c) AE technique has a far better degradation (pitting) monitoring capability compared to vibration and SOA techniques. These findings have made a vast contribution in condition monitoring of gearbox using AE technique and the proposed model has also offered opportunity to make AE a potentially viable and effective tool in diagnosis and prognosis of gearbox or even other rotating machinery defects.